(untitled) (Research, Society and Development, 2022)
Internal control contributes positively to the management process of public administration, as it ensures that administrative action is carried out efficiently. Therefore, this research aims to analyze how internal control can contribute to the public administration of a medium-sized company. The methodology consists of a quantitative exploratory research that carried out the application of a questionnaire with closed questions to the company’s employees, which was sent via e-mail, with a return of 53 company employees. The results indicated that employees are aware of the contributions and the important role that internal control plays in the company, and most respondents are fully aware of the contributions of the use of internal control in the execution of the organization’s activities. In this way, the study pointed out that it is necessary to devote greater attention to fraud and corruption prevention practices, aiming to contribute to the improvement of the management of the studied company.